2020
DOI: 10.1002/app.50145
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of superhydrophobic transparent cyclic olefin copolymer (COC)‐SiO2 nanocomposite surfaces

Abstract: A superhydrophobic cyclic olefin copolymer (COC) nanocomposite coating was produced with a very simple and easy method. Self-cleaning superhydrophobic COC surfaces were obtained by only adding surface hydrophobized SiO 2 nanoparticles by dip coating method. The influence of concentration of SiO 2 and the coating temperatures on the wettability of the surfaces were investigated. The surface wettability of the coatings was examined with the contact angle measurements and the surface roughness and morphology were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 72 publications
(195 reference statements)
1
13
0
Order By: Relevance
“…This situation showed that there was a transition behavior from the Wenzel model to the Cassie–Baxter model after from 1% Al 2 O 3 concentration. A similar transition behavior was given by several authors in the literature. ,, It was determined that the hysteresis values on glass, galvanized steel, and skin-passed galvanized steel surfaces were 9.9, 6.3, and 7.2 at 8% Al 2 O 3 concentration, respectively.…”
Section: Resultssupporting
confidence: 82%
See 3 more Smart Citations
“…This situation showed that there was a transition behavior from the Wenzel model to the Cassie–Baxter model after from 1% Al 2 O 3 concentration. A similar transition behavior was given by several authors in the literature. ,, It was determined that the hysteresis values on glass, galvanized steel, and skin-passed galvanized steel surfaces were 9.9, 6.3, and 7.2 at 8% Al 2 O 3 concentration, respectively.…”
Section: Resultssupporting
confidence: 82%
“…CAH was calculated by taking the difference between the advancing and receding contact angles (CAH = θ a – θ r ) and an important parameter to understand the movement of liquid droplets on solid surfaces. The Wenzel and Cassie–Baxter models are two classical models generally used for describing the wetting properties of superhydrophobic surfaces. ,,,, The equilibrium contact angle generally increases with increasing nanoparticle concentration due to the increasing surface roughness, but CAH behaves differently and oppositely in the two models. When the drop generally sticks strongly to the surface and CAH is large, it is defined as Wenzel mode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, the micro- and nanostructures formed by physical deposition are easily worn off by mechanical force, causing the loss of hydrophobic properties [ 26 ]. Additionally, although many techniques for constructing bionic rough surfaces have been developed, such as sol-gel [ 27 , 28 ], etching [ 29 , 30 ], self-assembly [ 31 , 32 ], deposition [ 33 , 34 , 35 ] and solution impregnation method [ 36 , 37 ], these methods often require harsh preparation conditions, special processing equipment and tedious operational steps. As a result, they are not suitable for industrialization or application in the water repellent finishing of cotton fabric [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%